2018
DOI: 10.1177/0300060518775290
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing outcomes in patients with subcortical stroke associated with lesions of the caudate nucleus and insula

Abstract: ObjectiveThe present study was performed to investigate the relationships between swallowing outcomes and lesion location, bolus characteristics, and age in patients with subcortical stroke.Patients: Patients with subcortical and insular stroke (mean age, 57.38 ± 12.71 years) were investigated. All patients (n = 21) completed both brain magnetic resonance imaging studies and videofluoroscopic swallowing studies.Main Outcome MeasuresThe oral transit duration, pharyngeal transit duration (PTD), laryngeal respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…In addition, stroke often causes deteriorations in sensory motor function, which can lead to longer swallowing initiation, decreased pharyngeal transport, and ineffective laryngeal protection (Mann, Hankey, & Cameron, 1999;Park, Kim, Ko, & McCullough, 2010;Seo, Oh, & Han, 2016). In demonstrating that advanced age is significantly associated with longer LRD, the results of the present study are in line with existing knowledge, and are similar to those of the prior investigation by Im, Jun, Hwang and Ko (2018) that showed a significant relationship between advanced age and longer LRD in subcortical stroke patients. Reduced swallowing efficiency in relation to longer swallowing duration has been a subject of discussion for a long time, and at least one reason for premature bolus loss in oropharyngeal swallowing impairment could be a longer LRD, especially with thin liquids (Kim & McCullough, 2007;Logemann et al, 1992;Park et al, 2010).…”
Section: Relationships Between Age Lesion Side Otd Ptd Lrd Lcd supporting
confidence: 91%
“…In addition, stroke often causes deteriorations in sensory motor function, which can lead to longer swallowing initiation, decreased pharyngeal transport, and ineffective laryngeal protection (Mann, Hankey, & Cameron, 1999;Park, Kim, Ko, & McCullough, 2010;Seo, Oh, & Han, 2016). In demonstrating that advanced age is significantly associated with longer LRD, the results of the present study are in line with existing knowledge, and are similar to those of the prior investigation by Im, Jun, Hwang and Ko (2018) that showed a significant relationship between advanced age and longer LRD in subcortical stroke patients. Reduced swallowing efficiency in relation to longer swallowing duration has been a subject of discussion for a long time, and at least one reason for premature bolus loss in oropharyngeal swallowing impairment could be a longer LRD, especially with thin liquids (Kim & McCullough, 2007;Logemann et al, 1992;Park et al, 2010).…”
Section: Relationships Between Age Lesion Side Otd Ptd Lrd Lcd supporting
confidence: 91%
“…The gradient of dopaminergic loss is largely preserved in all PD patients (Pasquini et al, 2019). Im et al (2018) and Kim et al (2019) showed that caudate damage can increase the risk of aspiration and prolong the recovery time of swallowing. Hence, caudate injury is likely involved in the occurrence of dysphagia in PD patients and is potentially associated with gradient changes in dopaminergic loss.…”
Section: Discussionmentioning
confidence: 99%
“…The median sample size was 95 (ranging from 20 to 342). Thirteen of the included studies were supratentorial strokes [ 11 , 12 , 13 , 17 , 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], one infratentorial stroke [ 36 ], and seven both the supratentorial and infratentorial strokes [ 16 , 37 , 38 , 39 , 40 , 41 , 42 ]. Besides, subjects of sixteen studies were in acute phase of stroke [ 11 , 12 , 13 , 14 , 16 , 17 , 25 , 29 , 34 , 35 , 38 , 39 , 41 , 42 , 43 , 44 ], one was in subacute phase of stroke [ 30 ], and one was in chronic phase of stroke [ 28 ], while the stroke phases of the remaining six studies were unclear ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The swallowing assessment tools included the Water Swallowing Test (WST) [ 11 , 43 ], Videofluoroscopic Swallowing Study (VFSS) (taking up 37.5% of included studies) [ 12 , 24 , 28 , 30 , 31 , 36 , 38 , 39 , 40 ], Volume-viscosity Swallow Test (V-VST) (4.2%) [ 43 ], Fiberoptic Endoscopic Evaluation of Swallowing (FEES) (12.5%) [ 29 , 42 , 44 ], MBS impairment tool (MBSImP) (4.2%) [ 13 ], Standardized Clinical Assessment Tool (4.2%) [ 25 ], and Bogenhausen Dysphagia Score Part 2 (BDS-2) (4.2%) [ 35 ]. A total of thirteen articles described the days to the evaluation of PSD (ranging from 24 h to 4 weeks; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation